2012
DOI: 10.1097/hjh.0b013e32834d9e0f
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria breakthrough under chronic renin–angiotensin–aldosterone system suppression

Abstract: These data indicate that a reappraisal of renin-angiotensin-aldosterone system (RAAS) suppression is required when microalbuminuria appears in patients under chronic RAAS suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…This enhanced risk was associated in many patients with the risk attributable to the presence of diabetes. This situation of risk can also be observed during chronic renin-angiotensin system blockade, as we previously described (36). The development of new-onset albuminuria during longterm administration of an ACE inhibitor or angiotensin receptor blocker is accompanied by an increased number of CVD events (36).…”
Section: Discussionmentioning
confidence: 78%
“…This enhanced risk was associated in many patients with the risk attributable to the presence of diabetes. This situation of risk can also be observed during chronic renin-angiotensin system blockade, as we previously described (36). The development of new-onset albuminuria during longterm administration of an ACE inhibitor or angiotensin receptor blocker is accompanied by an increased number of CVD events (36).…”
Section: Discussionmentioning
confidence: 78%
“…Patient selection and classification was previously described in an initial paper describing development of high albuminuria in patients during chronic RAS suppression [10].…”
Section: Patientsmentioning
confidence: 99%
“…Our group [10], among others, has described the development of de novo proteinuria during long-term antihypertensive therapy and particularly during chronic RAS suppression. In addition, a recent study conducted by our group has shown that well-controlled hypertensive patients who develop albuminuria under chronic RAS suppression, which besides are in an early stage of chronic kidney disease (CKD) development, present an increased oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…13 Briefly, 1143 patients were followed up for a minimum period of 3 years with visits to the Hypertension Unit, Hospital Universitario 12 de Octubre, Madrid, at least every 6 months. After that, the patients continued with their annual revisions.…”
Section: Patient Recruitmentmentioning
confidence: 99%